Odbiór audycji Rozgłośni Polskiej RWE w Polsce - Hajdasz, Jolanta (Pamięć i Sprawiedliwość, 2004)
The Polish Section of Radio Free Europe is one of language sections of Radio Free Europe/Radio Liberty, an American radio station which broadcasted its program from the FederalRepublic of Germany (Munich), Spain and Portugal for listeners in communist countries in Bulgarian, Czech, Polish, Slovak and Hungarian languages. The Polish section operated in 1952–1994. It has an unshakeable role in struggle for liberty and democracy in countries of the Soviet block. Radio Free Europe supported and shaped resistance against communist regimes in Eastern Europe. It is believed that its programs were commonlylistened to, despite intensive jamming. The article tries to define the number of listeners to the station. The author analyses currently available Polish and American source materials, which include results of researches conducted for Radio Free Europe which come from BIB (Board for International Broadcasting, an institution supervising the Radio since 1973 on behalf of the US Congress) and polls concerning receiving of Western radio stations broadcasting in Polish made by OBOP (Center for Public Opinion Polls) since 1969.